Two-step offer and return of multiple types of additional genomic findings to families after ultrarapid trio genomic testing in the acute care setting: a study protocol - Stephanie Best; Melissa Martyn; Ling Lee; Zornitza Stark; Ilias Goranitis; Marc Clausen; Yvonne Bombard; Martin Delatycki; Lilian Downie; Sebastian Lunke; Elly Lynch; Belinda Chong; et al. (BMJ Open, 2023)
Introduction As routine genomic testing expands, so too does the opportunity to look for additional health information unrelated to the original reason for testing, termed additional findings (AF). Analysis for many different types of AF may be available, particularly to families undergoing trio genomic testing. The optimal model for service delivery remains to be determined, especially when the original test occurs in the acute care setting.Methods and analysis Families enrolled in a national study providing ultrarapid genomic testing to critically ill children will be offered analysis for three types of AF on their stored genomic data: paediatric-onset conditions in the child, adult-onset conditions in each parent and reproductive carrier screening for the parents as a couple. The offer will be made 3–6 months after diagnostic testing. Parents will have access to a modified version of the Genetics Adviser web-based decision support tool before attending a genetic counselling appointment to discuss consent for AF. Parental experiences will be evaluated using qualitative and quantitative methods on data collected through surveys, appointment recordings and interviews at multiple time points. Evaluation will focus on parental preferences, uptake, decision support use and understanding of AF. Genetic health professionals’ perspectives on acceptability and feasibility of AF will also be captured through surveys and interviews.Ethics and dissemination This project received ethics approval from the Melbourne Health Human Research Ethics Committee as part of the Australian Genomics Health Alliance protocol: HREC/16/MH/251. Findings will be disseminated through peer-review journal articles and at conferences nationally and internationally.